Iatrogenic Burns - Burak Kaya; Bahadır Çelik; Cem Çerkez; Emrah Aslan; S. Elçin Işılgan; Savaş Serel (Turkish Journal of Plastic Surgery, 2016)
Iatrogenic burns are rare complications that can occur after using medical devices and chemicals in hospitals. Usually, these burns are deep and cause additional morbidity to patients. In this article, 6 iatrogenic burn patients referred to our department are presented, and predisposing factors and preventive measures are discussed.